Quality changes of squid (Loligo Sp.) during storage at ambient and chilled sea water temperatures. -- 1986 ; Sonia Y. De Leon , adviser. - Sensupa, Warunee
Squid (Loligo sp.) caught in February, 1985 and October 1985 in Manila Bay along the shores of Cavite kept for 12 hours in air at ambient temperature (26°-31°C); and for 5, 12 and 21 days in chilled sea water (CSW) at 10° , 5° and 0°C, respectively. Changes in sensory attributes of raw and cooked squids were determined and compared with changes in microbial counts; enterobacteriaceae count (only for samples held in air at ambient temperature), a total viable count (TVC) and hydrogen sulfide producers count (H2S producers count). Objective tests, such as hypoxanthine (Hx), K value, trimethylamine (TMA), total volatile nitrogen (TVN) and thiobarbituric acid (TBA) were also conducted. Sensory tests using trained panelists showed significant correlation with time for all of the samples. The microbial counts showed an increasing trend during storage periods. Squids were rejected when TVC reached 10^5 cfu/g for squids held in air at ambient temperature and 10^6, 10^8 and 10^8 cfu/g for squids held in CSW at 10°, 5° and 0°C, respectively. Enterobacteriaceae were important in the mesophilic spoilage of squid held in air at ambient temperature. At rejection, the enterobacteriaceae count was 10^5 cfu/g. H2S producers played major roles throughout the storage of squids held in CSW. Squids were considered spoiled when H2s producer counts reached 10^5, 10^7-8 and 10^7-8 cfu/g when stored in chilled sea water at 10° , 5° and 0°C, respectively. Objective tests results on Hx, K value, TMA and TVN were shown to be significantly correlated with the results of sensory evaluation of raw and cooked squids, as well as with storage time when squids were held in air at ambient temperature. The ranges of the rejection values under this condition were 3.69-3.97 u mole/g, 63.81-67.50%, 20.61-23.78 mg/100 g and 54.57-62.37 mg/100 g for Hx, K value, TMA and TVN, respectively. In contrast with squid held in air at ambient temperature, results of objective tests namely, Hx, K value, TMA and TVN of squids held in CSW did not show good correlation with time and with the sensory evaluation results. For the squid samples stored at 10°C hypoxanthine content decreased throughout the storage period. K values were also found to fluctuate as storage time progressed. Taste panelists rejected the samples at K values of 52.44-53.97%. Lower values at rejection were also obtained for TMA and TVN at the same storage temperature of 10°C than at ambient temperature. These values were 11.42-14.44 mg/100 g and 28.71-33.30 mg/100 g for TMA and TVN, respectively. For squid held in CSW at 5° and 0°C the Hx content, K value, TMA and TVN decreased during the later phase of the storage study when the samples approached incipient spoilage. TBA was not applicable for all of the samples due to the very low fat content of squid.